Corruption and Turnout in Presidential Elections: A Macro‐Level Quantitative Analysis. Issue 2 (2nd April 2013) - Stockemer, Daniel
<x xml:space="preserve">Abstract</x> This article tests the impact of corruption on electoral turnout for over 200 elections from over 70 presidential systems conducted between 1990 and 2011. Differentiating among three corruption indicators (i.e., the International Country Risk Guide corruption indicator, the Transparency International Corruption Perceptions Index, and the World Bank Control of Corruption measure), I evaluate corruption's precise impact on electoral participation in a pooled time series framework. Controlling for compulsory voting, semi‐presidentialism, regime type, development, political culture, the closeness of the election, and state size, my results are nuanced. I find that corruption more narrowly defined as political corruption stifles turnout, whereas a rather broad definition of corruption, which includes societal and financial corruption, has no impact on macro‐level turnout. Finally, I discover that the interactive impact of corruption on other variables in the turnout function is rather limited. Related Articles <mixed-citation id="polp12012-cit-0065" publication-type="journal" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink"> <string-name> <surname>Kostadinova</surname>, <given-names>Tatiana</given-names></string-name> <year>2009</year>. " Abstain or Rebel: Corruption Perceptions and Voting in East European Elections ." <source content-type="journalTitle">Politics & Policy</source><volume>37</volume> (<issue>4</issue>): <fpage>691</fpage>‐<lpage>714</lpage>. http://onlinelibrary.wiley.com/doi/10.1111/j.1747‐1346.2009.00194.x/abstract </mixed-citation> <mixed-citation id="polp12012-cit-0066" publication-type="journal" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink"> <string-name> <surname>Caillier</surname>, <given-names>James</given-names></string-name>. <year>2010</year>. " Citizen Trust, Political Corruption, and Voting Behavior: Connecting the Dots ." <source content-type="journalTitle">Politics & Policy</source><volume>38</volume> (<issue>5</issue>): <fpage>1015</fpage>‐<lpage>1035</lpage>. http://onlinelibrary.wiley.com/doi/10.1111/j.1747‐1346.2010.00267.x/abstract </mixed-citation> <mixed-citation id="polp12012-cit-0067" publication-type="journal" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink"> <string-name> <surname>Lagunes</surname>, <given-names>Paul F.</given-names></string-name> <year>2012</year>. " Corruption's Challenge to Democracy: A Review of the Issues ." <source content-type="journalTitle">Politics & Policy</source><volume>40</volume> (<issue>5</issue>): <fpage>802</fpage>‐<lpage>826</lpage>. http://onlinelibrary.wiley.com/doi/10.1111/j.1747‐1346.2012.00384.x/abstract </mixed-citation>